Role of Government Schemes in Women Empowerment and Socio-Economic Development in Uttar Pradesh - Yadav, Ankit; Prakash Yadav, Om; Singh, Kavita (Journal of Neonatal Surgery, 2025)
This paper analyses the role of government schemes in raising women empowerment and socio-economic development in Uttar Pradesh. The study examines the degree of scheme accessibility, its impact on education, financially and household autonomy and determines progress and existing gaps. Basically, recommendations involve awareness, implementation and structural support for inclusive development